Bồi dưỡng siêu nhận thức trong dạy học nội dung “Ứng dụng đạo hàm vào bài toán tối ưu” (Toán 12) - Nguyễn Ngọc Giang, Nguyễn Ngọc Giang; Nguyễn Ái Quốc, Nguyễn Ái Quốc; Hồ Lộc Thuận, Hồ Lộc Thuận (Tạp chí Giáo dục, 2026)
In the context of the renewed General Education Curriculum oriented toward competency development, fostering higher-order thinking skills in students, particularly in mathematics education, has become an essential requirement. However, students still face difficulties in applying derivatives to optimization problems due to limited abilities in self-regulation and cognitive monitoring. This study focuses on developing metacognition in teaching the topic “Applications of Derivatives in Optimization Problems” (Grade 12 Mathematics) to enhance learning effectiveness and mathematical thinking. Using theoretical research and content analysis methods, the paper clarifies the concept, structure, and role of metacognition, and proposes a teaching process aimed at fostering metacognitive development in students. The findings contribute to the theoretical foundation and provide practical solutions for innovating mathematics teaching methods in high schools.